Optimization of Hydrolyzed Pumpkin (Cucurbita Moschata) Starch as Natural Superdisintegrant in Promethazine HCl Sublingual Tablets - Winarti, Lina; Asrofi, Muhammad; Lubis, Maralodia Almira; Lestari, Tirtawati Putri; Sari, Lusia Oktora Ruma Kumala; Irawan, Eka Deddy; Febryanto, Hery Diar; Afthoni, Muhammad Hilmi; Eryani, Mikhania Christiningtyas (Science and Technology Indonesia, 2026)
Acid hydrolysis of pumpkin starch is a feasible strategy for developing novel pharmaceutical excipients, particularly natural superdisintegrants for sublingual and orally disintegrating tablet formulations. Given the requirement for extremely rapid tablet disintegration in sublingual dosage forms, selecting an efficient disintegrant is a critical formulation parameter. However, native pumpkin starch exhibits limited disintegration efficiency and generally requires high concentrations, which may adversely affect tablet hardness and friability. This study aimed to optimize the acid hydrolysis process of pumpkin starch and to evaluate the performance of the optimized hydrolyzed starch as a natural superdisintegrant in Promethazine HCl sublingual tablets. A factorial design was used to examine the impact of varying hydrolysis durations (3-9 days) and hydrochloric acid concentration (5-9%) on the physicochemical characteristics of the modified starch. The optimized hydrolyzed starch demonstrated a near-neutral pH (5.17 ± 0.03), acceptable moisture content (LOD 10.20 ± 0.44%), and excellent flow properties, as indicated by a low angle of repose (23.96°) and Carr’s index (9.99%). Scanning electron microscopy revealed increased surface irregularity and porosity, while FTIR analysis indicated enhanced exposure of hydroxyl groups, consistent with partial depolymerization of the starch polymer. The amylose content increased to 35.17%, accompanied by improved water uptake and swelling capacity. The effective pore radius (25.03 ± 0.35 µm) and swelling index (70.25 ± 0.57) were markedly higher than those of native pumpkin starch (12.27 µm and 44.30 ± 0.85, respectively), although slightly lower than crospovidone (27.65 µm and 99.97 ± 0.13). Incorporation of the hydrolyzed starch into Promethazine HCl sublingual tablets resulted in formulations with adequate mechanical strength (hardness 3.35 ± 0.05 kg), low friability (0.53 ± 0.04%), rapid disintegration (49.18 ± 0.75 s), and high drug release (96.79 ± 0.13%). These performances were comparable to those of crospovidone and superior to formulations containing native pumpkin starch. The improved tablet characteristics were primarily attributed to enhanced porosity and swelling capacity induced by acid hydrolysis. Overall, optimized hydrolyzed pumpkin starch demonstrates considerable potential as a sustainable, biodegradable, and cost-effective natural superdisintegrant for fast-disintegrating pharmaceutical tablet formulations.